Correction to: Providing dental insurance can positively impact oral health outcomes in Ontario - Nevena Zivkovic; Musfer Aldossri; Noha Gomaa; Julie W. Farmer; Sonica Singhal; Carlos Quiñonez; Vahid Ravaghi (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.